(untitled) (ENTHYMEMA, 2022)
Abstract – Book review of Moser, Keith, and Ananta Ch. Sukla, editors. Imagination and Art: Explorations in Contemporary Theory. Brill, 2020. Keywords – Theory of imagination; Aesthetic.